(untitled) (Marketing Journal, 2026)
The article scientifically analyzed the issue of forming and modeling the optimal structure of the regional economy. The study examined the structural proportions of № 1 -SON YANVA R, 202 6-YIL 562 the regional economic system, intersectoral balance, and the impact of resource allocation on economic efficiency based on an integrated approach. Econometric models, multifactor regression analysis, the input -output model, and optimization methods were ap plied to determine the optimal structure. The findings confirmed that investment, labor resources, innovation, and infrastructure significantly influenced regional structural changes. It was substantiated that sustainable regional development was ensured t hrough increasing diversification, expanding high value -added sectors, and scientifically grounded coordination of structural proportions.